High-Intensity Interval Training and Sprint-Interval Training in National-Level Rowers - Turner, Kirstie Jodie; Pyne, David Bruce; Périard, Julien D.; Rice, Anthony John (Frontiers in Physiology, 2021)
Purpose: The effects of two different high-intensity training methods on 2,000 m rowing ergometer performance were examined in a feasibility study of 24 national-level rowers aged 18–27 years (17 males, 2,000 m ergometer time trial 6:21.7 ± 0:14.6 (min:s) and seven females, 2,000 m ergometer 7:20.3 ± 0:12.1. Habitual training for all participants was ~12–16 h per week). Methods: 16 high-intensity ergometer sessions were completed across two 3-week periods. Participants were allocated into two groups according to baseline 2,000 m time. High-intensity interval session-sprint-interval session (HIIT-SIT) completed eight HIIT (8 × 2.5 min intervals; 95% of 2,000 m wattage) followed by eight SIT (three sets of 7 × 30 s intervals; maximum effort). SIT-HIIT completed eight SIT sessions followed by eight HIIT sessions. Both a 2,000-m time trial and a progressive incremental test finishing with 4 min “all-out” performance were completed before and after each 3-week phase. Results: Both groups showed similar improvements in 2,000 m time and 4 min “all-out” distance after the first 3 weeks (2,000 m time: HIIT-SIT: −2.0 ± 0.6%, mean ± 90% CL, p = 0.01; SIT-HIIT: −1.5 ± 0.3%, p = 0.01) with no significant difference between groups. HIIT-SIT demonstrated the greatest improvements in submaximal heart rate (HR) during the progressive incremental test with eight sessions of HIIT showing a greater reduction in submaximal HR than eight sessions of SIT. The net improvement of 16 high-intensity sessions on 2,000 m time was −2.5% for HIIT-SIT (−10.6 ± 3.9 s, p = 0.01) and − 2.2% for SIT-HIIT (−9.0 ± 5.7 s, p = 0.01) and for 4 min “all-out” performance was 3.1% for HIIT-SIT (36 ± 25 m, p = 0.01) and 2.8% for SIT-HIIT (33 ± 27 m, p = 0.01). Conclusion: Eight sessions of high-intensity training can improve 2,000 m ergometer rowing performance in national-level rowers, with a further eight sessions producing minimal additional improvement. The method of high-intensity training appears less important than the dose.